The Role Of Strategic Management In Optimizing Governance And Business Development Of Village-Owned Enterprises In The Digital Era - Arwin Sanjaya; Martani Huseini; Chandra Wijaya (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Village-owned enterprises hold a strategic role in driving economic empowerment and improving the welfare of rural communities. In the digital era, Village-Owned Enterprises face new challenges and opportunities influencing their management and business development. Effective strategic management is a crucial element in optimizing governance and accelerating business growth. This article aims to explore the role of strategic management in overcoming various challenges and harnessing the potential of digitalization to enhance the performance of Village-Owned Enterprises. The study employs a qualitative approach, focusing on several Village-Owned Enterprises in Indonesia that have implemented digital technologies in their management and business development processes. The findings reveal that adopting management information systems (MIS) and using digital platforms, such as e-commerce and social media, have significantly improved operational efficiency and governance transparency and expanded Village-Owned Enterprises's market reach to national and international levels. The study also identifies significant challenges faced by Village-Owned Enterprises, including limited human resources with digital skills, uneven telecommunications infrastructure, and insufficient funding for technology investment. Without adequate support, many Village-Owned Enterprises struggle to adopt technology effectively. Additionally, low digital literacy among managers and rural community members impedes the successful implementation of digital strategies. Based on these findings, the study emphasizes the importance of cross-sector collaboration involving the government, private sector, and local communities to accelerate digital transformation in rural areas. This includes enhancing internet infrastructure, providing digital skills training, and facilitating access to financing for technology investments.